Start-ups and the mobilization of social interactions - Barès, Franck; Cova, Bernard; Nemani, Anicet (Emerald Publishing Limited, 2023)
With this book comes a message that the authors have for management and entrepreneurship experts around the world. Beyond the myth of the 'start-up nation', 'hypergrowth', and speculation on future business value, there exists an alternative form of entrepreneurship that young entrepreneurs are embracing. They call it "entrepreneurial activism" and its philosophy is "community first, start-up second". Guiding entrepreneurs to reap the benefits of brand and market development, the authors present a five-step approach on how to develop a community and launch a start-up within it. This guide explores how best to define a cause and create a movement, to recruit volunteers and create opportunities within a community. The collaboration between the three authors creates an enticing mix of entrepreneurship and marketing perspectives that bridges the academic and professional worlds and shares a wealth of business expertise and experience from three continents.
Keywords: New business enterprises.; Social entrepreneurship.; Business & Economics -- New Business Enterprises.; Entrepreneurship.; elektronické knihy; electronic books